Model Interaksi Sosial dalam Forum Virtual - Abyan Arrasid; Anne Maryani (Bandung Conference Series: Communication Management, 2022)
Abstract. The development and progress of today's technology continues to grow rapidly. Modern technology allows users to fulfill their social needs without meeting face to face. Without realizing it, the human community has emerged in two worlds, namely real life and virtual life (cyber community). This study aims to determine how the model of social interaction in a virtual community on the Discord Channel "Rise of Monster Slayer (S.S.S)". Monster Slayer". This study uses a virtual ethnographic research method, namely research that involves ethnographers to participate as observers, either openly or secretly to observe what is happening in the virtual community space. The object in this study is the Discord Channel server " Rise of Monster Slayer (S.S.S)" as a virtual community. while the subjects involved were five people who were selected based on a purposive technique, with three main informants and two supporting informants. The results of this study show that the process of social interaction through virtual forums of user entities in the Rise of Monster Slayer server community generally uses a Mutual Discourse interaction model, where the identity of the entity as a communicator and communicant is fused and difficult to distinguish, therefore entities are considered as participants. Abstrak. Perkembangan dan kemajuan teknologi saat ini terus berkembang pesat. Teknologi modern memungkinkan pengguna memenuhi kebutuhan sosialnya tanpa harus bertatap muka. Tanpa disadari, komunitas manusia telah muncul di dua dunia, yaitu kehidupan nyata dan kehidupan maya (cyber community). Penelitian ini bertujuan untuk mengetahui bagaimana model interaksi sosial dalam komunitas virtual di Discord Channel “Rise of Monster Slayer (S.S.S)”. Monster Slayer”. Penelitian ini menggunakan metode penelitian etnografi virtual, yaitu penelitian yang melibatkan etnografer untuk berpartisipasi sebagai pengamat, baik secara terbuka maupun diam-diam untuk mengamati apa yang terjadi di ruang komunitas virtual. Objek dalam penelitian ini adalah server Discord Channel “ Rise Monster Slayer (S.S.S)” sebagai komunitas virtual. Sedangkan subjek yang terlibat adalah lima orang yang dipilih berdasarkan teknik purposive, dengan tiga informan utama dan dua informan pendukung. Hasil penelitian ini menunjukkan bahwa proses interaksi sosial melalui forum virtual entitas pengguna dalam komunitas server Rise of Monster Slayer umumnya menggunakan model interaksi Mutual Discourse, dimana identitas entitas sebagai komunikator dan komunikan menyatu dan sulit dibedakan, oleh karena itu entitas dianggap sebagai partisipan.